TI_GERICHTE 11.2019.27 vom 9. Dezember 2020 , Stralcio dal ruolo di un appello senza interesse pratico e attuale - TI Tribunale d'appello (2020)
Stralcio dal ruolo di un appello senza interesse pratico e attuale